2003
DOI: 10.1889/1.1832513
|View full text |Cite
|
Sign up to set email alerts
|

43.1: Color Filterless Liquid Crystal Display Illuminated with LEDs

Abstract: We have prototyped a 13.3‐inch diagonal color filterless LCD illuminated with LEDs. A new color directional backlight combined with a microlens attached liquid crystal cell plate shows the feasibility of a new power efficient LCD with better color and lead‐free features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…All the common factors affecting the LCD transmittance such as the polarizer transmittance are omitted in Eq. (8). T CF is the color-matched transmittance of the CFs.…”
Section: Optical Designmentioning
confidence: 99%
See 1 more Smart Citation
“…All the common factors affecting the LCD transmittance such as the polarizer transmittance are omitted in Eq. (8). T CF is the color-matched transmittance of the CFs.…”
Section: Optical Designmentioning
confidence: 99%
“…However, the FSCD turned out not to be easily commercialized, due to a problem related to the color breakup and the fast scan rate [7]. Taira et al [8] and Audran et al [9] reported an edge-lit color-filterless LCD that used a grating, a lenticular lens array, and a specially designed LGP. They were successful in removing the CF; however, it was very difficult to achieve good image quality without the CF.…”
Section: Introductionmentioning
confidence: 99%
“…The chip LEDs act as very small, almost point, sources on the entrance surface of the lightguide. The Lambertian emission profile results in rays emerging from the chip LED at many different angles within a hemisphere so only a very short mixing section is needed to realize the effectively white light [6].…”
Section: Light Sourcementioning
confidence: 99%
“…Yamada et. al proposed a color-filterless LCD employing an edge-lit backlight that belongs to the spatial-domain multiplexing technology [9]. They utilized a blazed grating and lenticular lens array (LLA) to separate the red, green, and blue (RGB) colors from the white backlight and then focus the RGB light onto the corresponding RGB subpixels of an LCD panel from which the CF had been removed.…”
Section: Introductionmentioning
confidence: 99%